PEMBERDAYAAN SDM UNTUK MENINGKATKAN KESEJAHTERAAN EKONOMI MASYARAKAT - Hardiantini, Ela; Erponis, Nuru Kalumidya; Septiani, Yeni (Indonesian Collaboration Journal of Community Services (ICJCS), 2025)
Human resource (HR) empowerment is a crucial step in improving the economic well-being of communities. In the context of community service, the theme "HR Empowerment to Improve Community Economic Welfare" focuses on strategic efforts to increase the capacity and quality of human resources, thereby creating sustainable economic opportunities for the community. In general, many communities are still hampered by limited education and skills. They require training and education tailored to market needs to compete in the workforce and manage their own businesses. Therefore, HR empowerment programs through practical skills training such as entrepreneurship, sustainable agriculture, business management, and technology utilization are crucial. These trainings aim to develop technical skills relevant to market needs while simultaneously supporting improved economic well-being. Furthermore, this program aims to raise community awareness of the importance of education and skills in achieving better economic opportunities. During the empowerment process, communities are involved in program planning and implementation, fostering a sense of ownership and motivation to implement the changes. With an approach involving training, mentoring, and access to economic opportunities, it is hoped that human resource empowerment will increase productivity and quality of life, while creating a more independent and sustainable economy. Through human resource empowerment, the economic well-being of communities can be significantly improved, which in turn will strengthen their competitiveness in facing global challenges.